Effectiveness of Students Independence Instruments Learning Cake Products and Indonesian Cake - Rahmah, Latifahtur; Nurlaela, Luthfiyah; Santosa, Agus Budi (Universitas Malikussaleh, 2019)
Independence is a needed skill in the 21st century. Learning independence will form a habit that will improve work skills. The focus of this research is to see the effectiveness of student independence instruments in learning cake products and Indonesian cake. The approach of this study is a qualitative approach with the trial subjects in this study involving 32 students of class XI Culinary 1 who were teaching cake products and Indonesian cake lessons at SMKN 8 Surabaya. The method used in this study is development research with a 4D model. The results of the validation of the instruments of the students' independence in the decoration material were on average material aspects of 4.36. The construction was 4.51, language or culture as well as 4.44. The assessment of the three validators of the students' independence instruments obtained the results of an average validation of 4.44 in the valid category. The result shows that the instrument was developed accordingly and can use as an instrument of student independence in Indonesian cake and cake product lessons. The reliability of the kappa coefficient for the three observers is 0.548 > 0.349. Based on the analysis carried out, it can conclude that the instrument tests the independence of independence and can use as an independent instrument for Indonesian cake and cake product lessons.